INTERNATIONAL EXPERIENCE IN ORGANIZING CASH ACCOUNTING AND DIRECTIONS FOR ITS IMPROVEMENT (International Congress on Economics, Management and Business Studies, 2026)
This article scientifically investigates the international experience in organizing cash accounting and the potential for its application within the national economy. In the global economy, the development of digital financial technologies, international accounting standards, and electronic payment systems is shaping modern mechanisms for cash accounting. Based on the experiences of the USA, Germany, Japan, and South Korea, the study analyzes the efficiency of cash flow accounting, internal control, electronic auditing, and digital financial management systems. Furthermore, the advantages of maintaining cash accounting based on International Financial Reporting Standards (IFRS) are highlighted. The impact of digital accounting systems on economic efficiency is assessed utilizing data from UNESCO, the World Bank, and international scientific databases. The ongoing reforms aimed at modernizing the accounting and financial control system in Uzbekistan are also analyzed. As a result of the research, scientific and practical recommendations have been developed for improving cash accounting in accordance with international standards.
Keywords: cash accounting, accounting, IFRS, electronic audit, financial control, digital economy, cash flow, financial management, electronic payment system, international experience, digital transformation, internal control.